Prediction of R + R2 gravity for the deflection of a photon passing close to the Sun - Accioly, A. [UNESP]; Ragusa, S.; De Rey Neto, E. C. [UNESP]; Mukai, H. (My University, 1999)
The cross-section for the scattering of a photon by the Sun's gravitational field, treated as an external field, is computed in the framework of R + R2 gravity. Using this result, we found that for a photon just grazing the Sun's surface the deflection is 1.75″, which is exactly the same as that given by Einstein's theory. An explanation for this pseudo-paradox is provided.